2015
DOI: 10.1103/physreve.92.052139
|View full text |Cite
|
Sign up to set email alerts
|

Generalized fluctuation theorems for classical systems

Abstract: Fluctuation theorems have a very special place in the study of non equilibrium dynamics of physical systems. The form in which it is used most extensively is the Gallavoti-Cohen Fluctuation Theorem[1] which is in terms of the distribution of the work p(W )/p(−W ) = exp(αW ). We derive the general form of the fluctuation theorems for an arbitrary Gaussian Markov process and find conditions when the parameter α becomes a universal parameter 1/kT . As an application we consider fluctuation theorems for classical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Following this, we will discuss a situation where the system (the oscillator) and the bath are connected via momentum-dependent couplings [48][49][50][51]; the specific case of a gauge-invariant model of a three-dimensional oscillator coupled to a heat bath via momentum variables in the presence of a vector potential is carefully analyzed [52,53]. Finally, we discuss the timely topic of fluctuation theorems [54][55][56][57][58][59][60][61][62][63][64][65], focusing on work fluctuations in the context of dissipative quantum oscillators, for such relations are intimately related to the second law of thermodynamics. As it turns out, for simple situations such as the Brownian motion as described by a linear Langevin equation which has a built-in noise term, the fluctuation theorem takes the simple form of the Gallavotti-Cohen kind [54,56,60].…”
Section: J Stat Mech (2024) 074002mentioning
confidence: 99%
See 2 more Smart Citations
“…Following this, we will discuss a situation where the system (the oscillator) and the bath are connected via momentum-dependent couplings [48][49][50][51]; the specific case of a gauge-invariant model of a three-dimensional oscillator coupled to a heat bath via momentum variables in the presence of a vector potential is carefully analyzed [52,53]. Finally, we discuss the timely topic of fluctuation theorems [54][55][56][57][58][59][60][61][62][63][64][65], focusing on work fluctuations in the context of dissipative quantum oscillators, for such relations are intimately related to the second law of thermodynamics. As it turns out, for simple situations such as the Brownian motion as described by a linear Langevin equation which has a built-in noise term, the fluctuation theorem takes the simple form of the Gallavotti-Cohen kind [54,56,60].…”
Section: J Stat Mech (2024) 074002mentioning
confidence: 99%
“…Finally, we discuss the timely topic of fluctuation theorems [54][55][56][57][58][59][60][61][62][63][64][65], focusing on work fluctuations in the context of dissipative quantum oscillators, for such relations are intimately related to the second law of thermodynamics. As it turns out, for simple situations such as the Brownian motion as described by a linear Langevin equation which has a built-in noise term, the fluctuation theorem takes the simple form of the Gallavotti-Cohen kind [54,56,60]. We analyze this for the case of the dissipative quantum cyclotron motion of a free particle and also its classical counterpart [60].…”
Section: J Stat Mech (2024) 074002mentioning
confidence: 99%
See 1 more Smart Citation
“…The statement reads: p{W }/p{−W } ∼ exp(αW ), where α is a positive temperature-dependent factor whose form is by no means universal. In fact, in [21] we showed that only for a one-dimensional process wherein the force acts on a single-component displacement vector does α reduce to 1/(K B T ) where K B is the Boltzmann constant. Now the question is: can one develop a similar formulation in the quantum case?…”
Section: Introductionmentioning
confidence: 95%
“…We have earlier shown the validity of the conventional fluctuation-dissipation theorems for the classical dissipative cyclotron motion described by Eq. ( 2) [21]. As stated before, here we examine if the fluctuation theorems are applicable to the quantized motion in a dissipative environment.…”
Section: Introductionmentioning
confidence: 99%